Microfoundations of accountability when transparency is constrained: moral and relational practices in Tonga's public sector - Iki Mafi Uele; Dinithi Ranasinghe; Chris Akroyd (Accounting, Auditing & Accountability Journal, 2026)
Purpose This study examines how accountability is enacted in everyday financial practice in Tonga's public sector by analysing the microfoundations through which public servants interpret, negotiate, and resolve accountability demands. It addresses an unresolved theoretical puzzle in accountability research: why strong moral responsibility can coexist with constrained procedural transparency. Rather than treating accountability outcomes as the product of institutional design alone, the study investigates how relational ethics, cultural obligations, and moral reasoning simultaneously enable accountability while limiting formal disclosure and contestation. Design/methodology/approach The study adopts a qualitative, interpretive research design grounded in talanoa, a Pacific dialogic methodology suited to eliciting morally and relationally embedded practices. Data were generated through in-depth talanoa with public servants across ministries and hierarchical levels in Tonga. Analysis follows a microfoundations perspective, tracing how individual-level moral judgements, emotional regulation, relational obligations, and discretionary practices aggregate into patterned organisational accountability outcomes. Findings The findings show that accountability in Tonga is enacted as a lived ethical practice rather than a purely procedural one. Moral self-regulation, faith-based responsibility, prudential judgement in budgeting, respect for hierarchy, and relational dialogue sustain strong accountability. At the same time, these same mechanisms constrain procedural transparency by discouraging escalation, formal contestation, and explicit disclosure. Accountability is therefore realised through a double-edged configuration in which moral responsibility is strengthened even as formal transparency becomes ethically, relationally, or politically costly. Originality/value The study contributes to accounting and accountability scholarship by offering a microfoundational explanation of why transparency deficits persist despite strong ethical commitment. It reframes constrained transparency not as an informational or enforcement failure, but as an outcome of morally embedded accountability practices. By theorising accountability as an emergent configuration of moral, emotional, and relational mechanisms, the paper advances understanding of how accountability is simultaneously enabled and constrained in relational public-sector contexts, with implications for accountability reform in developing and culturally plural settings.